2021
DOI: 10.5603/gp.a2020.0172
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity improves sleep quality in women

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
2
0
2
Order By: Relevance
“…The results of this study are therefore consistent with the existing literature about the benefits of exercise on insomnia severity [ 26 , 27 , 28 ]. In the study by Hartescu et al [ 29 ], after a 6-month moderate aerobic exercise program, participants decreased their ISI score by 4 points and 67% of participants in the PA group moved from clinical to subclinical insomnia.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are therefore consistent with the existing literature about the benefits of exercise on insomnia severity [ 26 , 27 , 28 ]. In the study by Hartescu et al [ 29 ], after a 6-month moderate aerobic exercise program, participants decreased their ISI score by 4 points and 67% of participants in the PA group moved from clinical to subclinical insomnia.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 1 depicts the detailed process of study selection. A total of 491 records were initially identified and 11 randomized controlled trials were included for synthesized analysis [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Study Selection and Extractionmentioning
confidence: 99%
“…In our study, the women's PA level was analyzed, and women are usually more willing to walk. Our results also showed that before and during COVID- Regular PA is an invaluable factor in improving the quality of life, controlling mood, reducing mental stress and alleviating menopausal symptoms [2,20]. The question of the influence of PA on COVID-19 infection is still an open question.…”
Section: Discussionmentioning
confidence: 60%